Recipient vaccine-associated paralytic poliomyelitis in China, 2010–2015. Issue 9 (21st February 2018) - Wu, Wendi; Wang, Huaqing; Li, Keli; Pekka Nuorti, J.; Liu, Dawei; Xu, Disha; Ye, Jiakai; Zheng, Jingshan; Fan, Chunxiang; Wen, Ning; An, Zhijie
Highlights: Before 2015, tOPV used to be the main vaccine in mainland of China for eradicating polio since 1978. To cope with WHO Polio End Game Strategy, polio vaccine switch program was implemented in China. This analysis was to understand the risk of VAPP after tOPV, using national AEFI surveillance data. Abstract: Introduction: Vaccine-associated paralytic poliomyelitis (VAPP) is one of the most important adverse effects of vaccines that are in current use globally. The Chinese national adverse event following immunization information system (CNAEFIS) is a passive surveillance system which collects data on VAPP. Aims: To describe the epidemiological characteristics of VAPP and estimate the risk of recipient VAPP in China. Methods: We retrieved information from reported cases of recipient VAPP from CNAEFIS from 2010 to 2015, examined the demographic characteristics of the cases, and used administrative data on vaccination doses and the estimated number of births as denominators to calculate VAPP incidence. Results: During 2010–2015, 157 cases of recipient VAPP were reported to CNAEFIS (male-to-female ratio, 8.2:1); 151 cases (96.2%) were less than six months old. All cases were associated with trivalent OPV (tOPV), and 89.8% occurred after the receipt of first dose. Of the 157 recipient VAPP cases, type II, type III, and type I poliovirus vaccine strains were isolated from 27 (17.2%), 25 (15.9%), and 16 (10.2%) cases, respectively. One case died and one case recovered completely; the other 155 cases had various physical disabilities, such as monolateral or bilateral limping. Using the administered doses of OPV as the denominator, the incidence of recipient VAPP during the study period was estimated at 0.4 per million doses. The estimated recipient VAPP per million births ranged from 1.0 to 2.4 during 2010–2015. Conclusion: The epidemiological characteristics of recipient VAPP cases in China, such as age distribution, were comparable to those in previous studies from other countries. The risk of recipient VAPP, using either estimated births or vaccination doses, was comparable to that in the US and Japan. We recommend using an inactive poliovirus vaccine to decrease the number of recipient VAPP cases in China.